Pusat Pelatihan Pencak Silat Dengan Pendekatan Arsitektur Metafora - Kurniawan, Eka; Hidayat, Wahyu; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pencak Silat is an Indonesian martial art which is an ancestral heritage that must be maintained and defended. Rokan Hilir including one of the areas that still keep the art of Pencak Silat, it is proven there are still some universities that still preserve martial arts, which has hundreds of students and even successfully create athletes who excel. But there is no training center that canaccommodate the athlete's training specifically and the availability of good athletes coaching facility, so that the activity of coaching becomes limited. This makes the regeneration of Rokan Hilir athletes difficult to develop and impact on unsatisfactory achievement. For that we need a building that meets the ideal conditions as a place of education and training. The design of this Training Center with the theme of Architecture Metaphor, aims to adjust the concept of design as the object of one of Pencak Silat motion is